Laser Microprobe Mass Analysis (LAMMA) as a Method for the Identification of Inorganic Substances - José Dennemont; Jean-claude Landry; Josianne Jaccard (CHIMIA)
LAMMA, the Laser Microprobe Mass Analysis, is a fast and sensitive technique that has found many applications in chemistry. The characterization of inorganic compounds by this technique, however, is limited by a lack of understanding regarding the formation of ions. Indeed, after laser-induced ionization one cannot talk of the fragmentation pattern of the molecules, instead cluster formation and recombination reactions prove to be the commonly observed feature. As a result most of the interpretation so far has been done by way of comparison or «fingerprint» matching. – In this account we report on the work carried on in our laboratory with a view to understanding the mechanism of ion formation. The interpretation of unknowns in the light of present knowledge is discussed with special reference to the nitrates, halides, and silicates. For example the three most common types of asbestos fibres (chrysotile, amosite, and crocidolite) are easily identified and differentiated from each other and the other asbestos fibres.